Lewin's Cells - George Plopper [ editor ] (Jones & Bartlett India Pvt.Ltd., 2015)
Ideal text for undergraduate and graduate students in advanced cell biology courses Extraordinary technological advances in the last century have fundamentally altered the way we ask questions about biology, and undergraduate and graduate students must have the necessary tools to investigate the world of the cell. The ideal text for students in advanced cell biology courses, Lewin's CELLS, Third Edition continues to offer a comprehensive, rigorous overview of the structure, organization, growth, regulation, movements, and interactions of cells, with an emphasis on eukaryotic cells. The text provides students with a solid grounding in the concepts and mechanisms underlying cell structure and function, and will leave them with a firm foundation in cell biology as well as a "big picture" view of the world of the cell. Revised and updated to reflect the most recent research in cell biology, Lewin's CELLS, Third Edition includes expanded chapters on Nuclear Structure and Transport, Chromatin and Chromosomes, Apoptosis, Principles of Cell Signaling, The Extracellular Matrix and Cell Adhesion, Plant Cell Biology, and more. All-new design features and a chapter-by-chapter emphasis on key concepts enhance pedagogy and emphasize retention and application of new skills. Thorough, accessible, and essential, Lewin's CELLS, Third Edition, turns a new and sharper lens on the fundamental units of life